العلاقة بين الزواج المبكر وأمراض عنق الرحم - سلمان, صفاء; رمضان, لينا; الحنون, بدور (Latakia University Journal -Medical Sciences Series, 2017)
أجري البحث في قسم التوليد وأمراض النساء بمشفى الأسد الجامعي في اللاذقية في الفترة الواقعة بين (1/1/2014) – (30/6/2015 ). شمل البحث ( 100 ) مريضة, أجريت لهن لطاخة بابانيكولاو وتنظير عنق رحم مكبر، وذلك لتحري تأثير ( الزواج المبكر ) على الموجودات التنظيرية والخلوية لعنق الرحم.وتمت مقارنة النتائج بين: عينة المتزوجات بعمر مبكر (أصغر من 20 سنة) , 50 مريضة غير المتزوجات بعمر مبكر (أكبر من 20 سنة) , 50 مريضةوتبين لدينا بالمقارنة بين المجموعتين وجود فرق في نسبة الموجودات التنظيرية الشاذة:حيث كانت النسبة في عينة المتزوجات باكراً: ( 26% )في حين كانت النسبة في عينة غير المتزوجات باكراً: (12% )كما تبين وجود فرق بين المجموعتين في نسبة الموجودات الخلوية الشاذة: حيث كانت النسبة في عينة المتزوجات باكراً: ( 18% ) في حين كانت النسبة في عينة غير المتزوجات باكراً: (8%)وهذا يؤكد دور ( الزواج المبكر ) في زيادة الموجودات التنظيرية والخلوية الشاذة لعنق الرحم مع التأكيد على أهمية الكشف الدوري باللطاخة وتنظير عنق الرحم المكبر.The research was conducted in the department of obstetrics and gynecology at Al-Assad university hospital in Lattakia in the period between (1/1/2014) – (30/6/2015). The study included (100) patient, who submitted to colposcopy and Papanicolaou smear to detect the effect of early marriage (early onset of sexual activity) on colposcopic and cellular finding in cervix .The results in (early married women) group (50) patient were compared to control group from patients who (not early married women)group (50) patient.We found that there was important difference in the rate of abnormal colposcopic findings : This rate in early married women was (26%) and in the second was (12%). We also found that there was important difference in the rate of abnormal cellular findings: This rate in early married women was (18%) and in the second was (8%). This assure the effect of early onset of sexual activity (early marriage) on colposcopical and cellular finding in cervix with assuring on the importance of frequent colposcopy and Papanicolaou smear test.